Counter Selection Substrate Library Strategy for Developing Specific Protease Substrates and Probes. Issue 8 (18th August 2016) - Poreba, Marcin; Solberg, Rigmor; Rut, Wioletta; Lunde, Ngoc Nguyen; Kasperkiewicz, Paulina; Snipas, Scott J.; Mihelic, Marko; Turk, Dusan; Turk, Boris; Salvesen, Guy S.; Drag, Marcin
Summary: Legumain (AEP) is a lysosomal cysteine protease that was first characterized in leguminous seeds and later discovered in higher eukaryotes. AEP upregulation is linked to a number of diseases including inflammation, arteriosclerosis, and tumorigenesis. Thus this protease is an excellent molecular target for the development of new chemical markers. We deployed a hybrid combinatorial substrate library (HyCoSuL) approach to obtain P1-Asp fluorogenic substrates and biotin-labeled inhibitors that targeted legumain. Since this approach led to probes that were also recognized by caspases, we introduced a Counter Selection Substrate Library (CoSeSuL) approach that biases the peptidic scaffold against caspases, thus delivering highly selective legumain probes. The selectivity of these tools was validated using M38L and HEK293 cells. We also propose that the CoSeSuL methodology can be considered as a general principle in the design of selective probes for other protease families where selectivity is difficult to achieve by conventional sequence-based profiling. Graphical Abstract: Highlights: CoSeSuL approach as a new tool for developing legumain-selective substrates and ABPs Unnatural amino acids increase selectivity of synthetic legumain substrates MP-L01 is a potent and selective cell-permeable legumain probe Abstract : Poreba et al. developed a new chemical strategy (Counter Selection Substrate Library, CoSeSuL) to obtain very selective legumain substrates and activity-based probe (MP-L01) for the direct inhibition and visualization of this protease in living cells. MP-L01 does not cross-react with caspases.